Managing start-up – incumbent digital solution co-creation : a four-phase process for intermediation in innovative contexts - Garcia Martin, Patricia Carolina; Sjödin, David; Nair, Sujith; Parida, Vinit (Taylor & Francis Group, 2023)
As incumbents strive to collaborate with start-ups in the pursuit of cutting-edge digital solutions, the complexities posed by disparate partners and their innovative endeavours often lead to intricate tensions. Our research underscores the critical role of innovation intermediaries in enabling a successful digital co-creation, yet a deeper understanding of this novel and evolving context is required. Through a comprehensive study of two innovation intermediaries, five incumbent companies, and eleven start-ups, we shed light on how intermediaries can effectively mitigate the hard-to-manage tensions that emerge. Our analysis uncovers three primary tensions: incompatible digital co-creation cultures, divergent digital innovation operations, and misaligned technical capabilities. We further propose a four-phase process for innovation intermediation, including the establishment of digital co-creation foundations, catalysing digital innovation projects, orchestrating the co-creation process, and scaling the resulting outcomes.
Keywords: Tension mitigation; innovation orchestration; asymmetric collaboration; value co-creation; digitalisation; fi=Strateginen johtaminen|en=Strategic Management|